The Student's Perspective Concerning the Regional Language Maintenance at Universitas Kristen Indonesia - Gunawan Tambunsaribu (Universitas Cokroaminoto Palopo, 2025)
The researcher aims to examine the perspectives of Universitas Kristen Indonesia students who come from outside Jakarta regarding maintaining their regional languages. The researcher wants to determine which regional languages of the islands are included as the top 10 regional languages best known by Indonesian Christian University students. He also wants to know the activities conducted by the students to maintain or maintain their regional languages when they live in Jakarta. The researcher uses a qualitative method with a descriptive approach. The research uses interviews as the technique to obtain data. The respondents in this research were the students from the Universitas Kristen Indonesia who came from different islands and archipelago. The respondents were 20 students, who came from 5 islands and 4 archipelagos in Indonesia, namely Sumatra Island, Java Island, Kalimantan Island, Sulawesi Island, Papua Island, Riau Islands, Bangka Belitung Islands, Nusa Tenggara Islands, Maluku Island. Based on the findings, it is found that one of the factors why the students who came from outside Jakarta still speak their regional language is because they join some communities in which the members are from the same villages and use the same regional language as they do.